Assessment of adherence to dietary recommendations and associated factors among type 2 diabetic patients in selected hospitals in Addis Ababa, Ethiopia - Atinafu, Wabi Temesgen; Tilahun, Kefyalew Naniye (Frontiers in Nutrition, 2025)
BackgroundIn Ethiopia, diabetes and its complications are significant causes of morbidity and mortality, with huge economic implications. Despite the high dietary non-adherence that has been reported in limited studies in Ethiopia. Moreover, there is a gap from the perspective of patients in the area of this topic.ObjectivesThis study aimed to assess adherence to dietary recommendations and associated factors among type 2 diabetic patients in Addis Ababa Selected Hospitals, Addis Ababa, Ethiopia, 2024.Methods and materialsAn institution-based cross-sectional study was conducted in a 420 sampled population among four hospitals found in Addis Ababa, Ethiopia, from 24 June to 15 July 2024. Systematic random sampling was used to recruit individual study participants. The collected data were exported into SPSS version 25 software for analysis. A descriptive summary, including frequencies, percentages, and graphs, was used to present the study results. Binary logistic regression was used for statistical analysis. Finally, the results of bivariate and multivariable logistic regression analyses were presented using odds ratios with 95% confidence intervals. In the final model, a p-value of <0.05 was taken as statistically significant.ResultsA total of 406 participants were included, with a response rate of 96.7%. The study participants had an average age of 48 (± 11.4 years), and the overall adherence to dietary recommendations in this study was 62.8% among type 2 diabetic patients. Years of diagnosis of DM, having a family history of DM, having comorbidities, and having received diabetic nutrition education were significantly associated with adhering to diabetic dietary recommendations among type 2 diabetic patients.Conclusion and recommendationThe study found that overall adherence to dietary recommendations among type 2 diabetic patients was relatively high at 62.8%, suggesting the need to develop and implement tailored dietary education and counseling programs for this patient population.